2021
DOI: 10.1021/acs.jpclett.1c02955
|View full text |Cite|
|
Sign up to set email alerts
|

Elucidation of SARS-Cov-2 Budding Mechanisms through Molecular Dynamics Simulations of M and E Protein Complexes

Abstract: SARS-CoV-2 and other coronaviruses pose major threats to global health, yet computational efforts to understand them have largely overlooked the process of budding, a key part of the coronavirus life cycle. When expressed together, coronavirus M and E proteins are sufficient to facilitate budding into the ER-Golgi intermediate compartment (ERGIC). To help elucidate budding, we ran atomistic molecular dynamics (MD) simulations using the Feig laboratory’s refined structural models of the SARS-CoV-2 M protein dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…Despite the M protein dimer being crucial for various biological functions such as SARS-CoV-2 virion assembly and shape formation [ 63 ], the type of interactions established in its homodimer form are still poorly understood [ 9 , 12 ]. Experimental SARS-CoV M protein dimer data demonstrated that residues W19, W57, P58, W91, L92, Y94, F95, and C158 were relevant, suggesting that homologous residues W20 (TMH1 domain), W58, and P59 (TMH2 domain), and W92, L93 Y95, and F96 (TMH3 domain) of SARS-CoV-2 may also be important for M dimer interaction and stabilization [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the M protein dimer being crucial for various biological functions such as SARS-CoV-2 virion assembly and shape formation [ 63 ], the type of interactions established in its homodimer form are still poorly understood [ 9 , 12 ]. Experimental SARS-CoV M protein dimer data demonstrated that residues W19, W57, P58, W91, L92, Y94, F95, and C158 were relevant, suggesting that homologous residues W20 (TMH1 domain), W58, and P59 (TMH2 domain), and W92, L93 Y95, and F96 (TMH3 domain) of SARS-CoV-2 may also be important for M dimer interaction and stabilization [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, this region seems to be the best candidate area for the development of a new drug/peptide to inhibit SARS-CoV-2 M protein dimer formation. This zone was also a promising target in another approach that searched for druggable targets in the homodimeric structure [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…All-atom molecular dynamics simulations provide powerful analytic tools in analyzing protein–protein interactions. However, because these processes represent miniscule portions of an immensely larger enterprise and occur over time scales on the order of nanoseconds, they are nearly impossible to apply to the entire assembly and budding process [ 30 , 31 , 32 ]. To this end, coarse-grained (CG) modeling has been employed to explore the kinetics of assembly of spherical icosahedral viruses.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with Kuzmin et al‘s work, where the authors found that the induction of membrane curvature by the E protein led to thinner membrane close to the TM regions but thicker around the CTDs ( Kuzmin et al, 2022 ). Yet, another study by Collins et al found that the E protein was not able to facilitate membrane curvature ( Collins et al, 2021 ). These inconsistent results might arise from the different protein structural models (Heo and Feig’s predicted model ( Heo and Feig, 2020 ) vs. our refined model generated from MD simulations) or the different membrane systems used in the studies (ERGIC mimic vs. pure POPC).…”
Section: Resultsmentioning
confidence: 99%